2019
DOI: 10.1111/nph.15712
|View full text |Cite
|
Sign up to set email alerts
|

SPL7 and SPL8 represent a novel flowering regulation mechanism in switchgrass

Abstract: Summary The aging pathway in flowering regulation is controlled mainly by microRNA156 (miR156). Studies in Arabidopsis thaliana reveal that nine miR156‐targeted SQUAMOSA PROMOTER BINDING‐LIKE (SPL) genes are involved in the control of flowering. However, the roles of SPLs in flowering remain elusive in grasses. Inflorescence development in switchgrass was characterized using scanning electron microscopy (SEM). Microarray, quantitative reverse transcription polymerase chain reaction (qRT‐PCR), chromatin immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 66 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…These observations indicated that a subset of VcSBP s might be involved in the regulation of chlorophyll accumulation. Previous studies have revealed that SBP family proteins can directly interact with their clients (for example, AtFUL , AtSOC1 , AtDFR , AtAP1 , MdWRKY100 , MaLCYB1.1 , and MaLCYB1.2 , MADS5 , and MADS32 ), thereby regulating diverse biological processes in plants such as flowering, inflorescence formation, biosynthesis of secondary metabolites, root regeneration, and response to stress ( Yamaguchi et al, 2009 ; Gou et al, 2019 ; Ma et al, 2020 ; Zhu et al, 2020 ). However, the targets of SBP proteins associated with chlorophyll accumulation have remained to be found.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated that a subset of VcSBP s might be involved in the regulation of chlorophyll accumulation. Previous studies have revealed that SBP family proteins can directly interact with their clients (for example, AtFUL , AtSOC1 , AtDFR , AtAP1 , MdWRKY100 , MaLCYB1.1 , and MaLCYB1.2 , MADS5 , and MADS32 ), thereby regulating diverse biological processes in plants such as flowering, inflorescence formation, biosynthesis of secondary metabolites, root regeneration, and response to stress ( Yamaguchi et al, 2009 ; Gou et al, 2019 ; Ma et al, 2020 ; Zhu et al, 2020 ). However, the targets of SBP proteins associated with chlorophyll accumulation have remained to be found.…”
Section: Discussionmentioning
confidence: 99%
“…SPL genes are very important for plant growth and development, as they regulate the specific downstream gene expression, such as the phase transition from vegetative to reproductive, trichome development, leaf development, fruit ripening, pollen sac development, fertility, plant hormone signaling [ 11 , 12 , 13 ], toxin resistance [ 14 ], copper deficiency response [ 15 ], temperature, salinity, and drought stress tolerance [ 7 , 16 ]. In addition, SPLs are targeted by miR156 family members [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, AtSPL9 (squamosa promoter binding protein-like) controls the initiation of cauline leaf axillary meristems (Tian et al, 2014). In transgenic M. truncatula plants overexpressing MtSPL8 inhibits branching by directly suppressing axillary bud formation (Gou et al, 2018). Down-regulation MsSPL8 increases branch density and enhances drought and salt tolerance in transgenic alfalfa (Gou et al, 2018).…”
Section: Morphological and Physiological Regulation Of Drought Tolerancementioning
confidence: 99%
“…In transgenic M. truncatula plants overexpressing MtSPL8 inhibits branching by directly suppressing axillary bud formation (Gou et al, 2018). Down-regulation MsSPL8 increases branch density and enhances drought and salt tolerance in transgenic alfalfa (Gou et al, 2018). Interestingly, M. truncatula plants with upregulated MtRAV3 (related to ABI3/VP1 transcription factor) have the similar tolerance to drought and salt stress, but exhibiting dwarfing, late flowering, and smaller leaves (Wang S. et al, 2021).…”
Section: Morphological and Physiological Regulation Of Drought Tolerancementioning
confidence: 99%
See 1 more Smart Citation